URGENSI PROGRAM LEGISLASI DESA GUNA MEMBENTUK PERATURAN DESA YANG ASPIRATIF - Mujiyana; Septi Nur Wijayanti (Universitas Muhammadiyah Yogyakarta, 2018)
Tamantirto and Ngestiharjo village are lowland villages which developing society. Plural societyeffected bythe number of immigrants domiciled in the region. Tamantirto Village and NgestiharjoVillage are lowland villages where the condition of the society has started to develop modern life.The community is very diverse as a result of the many immigrants who are domiciled in the region.The main livelihoods of most residents of Ngestiharjo and Tamantirto Villages are farmers andentrepreneurs as well as civil servants and private. This raises many needs of the community alongwith the increasing complexity of the problems encountered. Therefore, an aspirational regulationthat regulates the complexity of the problems in both villages is needed. The purpose of thisdedication is to create an indispensable quality and aspirational village rule with the establishmentof a Prolegdes and a review before the establishment of a village rule. Due to the limited knowledgeof legal drafting and conducting academic studies it is imperative that empowerment programsbe undertaken on BPD and village apparatus and village heads. Methods of dedication undertakenthrough a series of training activities, the establishment of prolegdes, conducting academic studiesas well as ongoing assistance. The results of this service were identified by the problems thatemerged in the two villages, which should then be followed up with the preparation of the DIM(Problem Inventory List) and a 1 year village legislation program was established in both villages.